Excavations at Castlehill of Strachan, 1980-1 - Yeoman, Peter A; Boyd, W E; Duncan, H B; Gemmell, A M D; Hodgson, G W I; Hulme, P D; Murray, Hilary; Murray, J C; Shirriffs, Jennifer; Simpson, Grant G; et al. (Proceedings of the Society of Antiquaries of Scotland, 1985)
A typical northern motte had a timber hall on the summit, two phases of palisade, surrounding ditch and approach causeway. The 13th century landscape was reconstructed using geomorphology and air photography. Coins, pottery of c 1250 to early 14th. Three furnaces/ovens were set on reused millstones. Metalwork, animal bones, pottery, palaeobotany.